2016
DOI: 10.19044/esj.2016.v12n9p333
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation Des Attaques De Termites (Isoptera Brulle, 1832) Sur Quatre Essences Forestieres D’importance Economique Au Togo (Afrique De L’ouest)

Abstract: Termites are one of the most abundant invertebrates in tropical ecosystems, where they play a major ecological role in litter decomposition. Despite their important role, termites can cause considerable damage to wood structures in most tropical countries. The aims of this study was to evaluate termite attack in four economically important species in Togo including Antiaris africana Engl (Moraceae), Pterocarpus erinaceus Poir (Fabaceae), Triplochiton scleroxylon Schum (Malvaceae) (all local species) and teak o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…This inability to occupy all of their niche is due to the importance of other environmental constraints such as soil, vegetation, competition between plant species, wildfires, grazing, human activities, etc (Ivory and Russell, 2016;Trisurat and Eawpanichet Kalliola, 2016;Lavorel et al, 2007). P. erinaceus trees are also attacked by termites as Amitermes evuncifer, Ancistrotermes guineensis and Microtermes lepidus (Gbenyedji et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…This inability to occupy all of their niche is due to the importance of other environmental constraints such as soil, vegetation, competition between plant species, wildfires, grazing, human activities, etc (Ivory and Russell, 2016;Trisurat and Eawpanichet Kalliola, 2016;Lavorel et al, 2007). P. erinaceus trees are also attacked by termites as Amitermes evuncifer, Ancistrotermes guineensis and Microtermes lepidus (Gbenyedji et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…A . evuncifer causes considerable damage in teak plantations [59]. This widespread occurrence implies that they are generalists with low habitat requirements.…”
Section: Discussionmentioning
confidence: 99%
“…Anani Kotoklo et al (2010b) observed that the incidence and intensity of termite attacks vary according to the species, the locality and the edaphic factors. Termite attacks can be related on nature of soil (ferralitic red soil) that would favour the installation of termite mounds, sources of plant infestations (Gbenyedji et al, 2016). The study showed that intermediate systems are the least attacked by termites, especially those close to shaded systems.…”
Section: 2mentioning
confidence: 93%
“…Indeed, most termites build veneers on the trunks of plants. These veneers serve as protection to attack the plant (Gbenyedji et al, 2016). The evaluation of termite attack rates showed that attacks were more common in full sun systems (61.49%), while in intermediate management systems were the least attacked.…”
Section: 2mentioning
confidence: 99%